Portal Vein Thrombosis due to Prothrombin Gene Mutation following Sleeve Gastrectomy - Murad Baba; Jordan Fakhoury; Amer Syed (Case Reports in Gastrointestinal Medicine)
Introduction. Portomesenteric thrombosis is increasingly recognized as a complication of laparoscopic sleeve gastrectomy (LSG). It often presents with abdominal pain. We present a mother and her son who both developed portal vein thrombosis (PVT) after LSG. Case Description. A 43-year-old woman presented complaining of sudden severe abdominal pain, two weeks after she had uncomplicated laparoscopic sleeve gastrectomy. CT scan of the abdomen and pelvis with IV contrast showed portal vein thrombosis and SMV thrombosis. Two weeks later her son had the same LSG for morbid obesity and presented with the same clinical picture. Thrombophilia workup showed heterozygous prothrombin gene mutation. Conclusions. A high index of suspicion is necessary to diagnose PVT; although rare, it can be potentially lethal. Anticoagulation therapy should be initiated immediately to limit the morbidities and improve the outcome. Patients with family history of thrombophilia should be investigated prior to any bariatric surgery and nonsurgical alternative treatments for morbid obesity should be strongly encouraged.